إدارة المــعرفة كاداة لتمنية الميزة التنافسية في المنظمة الخدمية -دراسة حالة مؤسسة اتصالات الجزائر- - رشام, كهينه; جميل, أحمد (جامعة الوادي University of Eloued, 2018)
This study attempts to design and develop a model for the impact of knowledge management on the development of competitive advantage in the service organization and to try to survey it through a field study on the Algerian Telecom Corporation. The study model is determined by an independent variable represented in Knowledge Management, In order to achieve the objectives of the study, a questionnaire was designed and developed for the purpose of collecting data from the individuals of the research sample. It reached 68 individuals. The Statistical Package for Social Sciences (SPSS) was used to analyze the data statistically, based on simple regression analysis and other statistical methods. The study concluded that there is a positive effect of the independent variable (knowledge management) on (competitive advantage). The study recommends that attention should be paid to developing the dimensions of knowledge management in the research company and creating the appropriate environment for adopting such modern concepts
مقال
Keywords: المعلومة، إدارة المعرفة، الميزة التنافسية، المنظمة الخدمية.; information, knowledge management, competitive advantage, service organization